Effects of a selective sleep deprivation on subsequent anaerobic performance - Mougin, F.; Bourdin, H.; Simon-Rigaud, M. L.; Didier, J. M.; Toubin, G.; Kantelip, J. P. (International Journal of Sports Medicine, 1996)
The aim of the study was to investigate the effects of a partial sleep deprivation on a subsequent supramaximal exercise evaluated from the 30 second Wingate test, and on the following recovery. To take into account the active muscle mass, the Wingate test was performed against a constant braking force related to the data of a force-velocity test conducted on a Monark cycle ergometer (Model 814 E with weights) one week before the experimental test. Eight highly trained athletes were enrolled for this study. The changes in ventilatory and metabolic responses were analyzed during and upon completion of physical 30 second exercise, taking place after two nights, in other words, after a reference night and after a night with reduced sleep. Partial sleep deprivation was obtained by delaying bedtime until 3 a.m. The 30 second Wingate test was performed between 9 a.m. and noon the following days, using a Monark ergometer (Model 814 F). The analyses of change scores disclosed that there were no main significant effects for measures of ventilation, lactates and pH(v) levels under the two experimental conditions. The peak power, the mean power output and the peak velocity recorded after partial sleep deprivation were not modified in comparison with the values obtained after the reference night. These findings suggest that acute sleep loss did not contribute to alterations in supramaximal exercise.